2022
DOI: 10.1007/978-981-16-6791-6_16
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Use of Green Spaces by Citizens Before and During the First COVID-19 Pandemic: A Big Data Analysis Using Mobile-Tracking GPS Data in Kanazawa, Japan

Abstract: To consider green spaces and parks as valuable green infrastructure that provides various socio-ecological benefits, including health, this study analyzed changes in the use of green spaces before and during the first COVID-19 pandemic in Japan, using mobile-tracking GPS data of Kanazawa citizens. The results showed that the declaration of a state of emergency in April–May 2020 changed the outing behavior of Kanazawa citizens, and there was a strong tendency for them to avoid going out, with a decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…In the UK and New Zealand, there is a significant increase in green space visits as lockdown restrictions eased, indicating people’s willingness to visit urban green spaces. Another study found that pedestrian activity increased in city parks, peri-urban forests, and protected areas in Kanazawa, Japan, during public park closures ( 34 ). Furthermore, studies have shown that visiting urban green spaces during the COVID-19 pandemic did not increase the risk of infection, although context-specific measures should be considered to ensure the safety of visitors ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the UK and New Zealand, there is a significant increase in green space visits as lockdown restrictions eased, indicating people’s willingness to visit urban green spaces. Another study found that pedestrian activity increased in city parks, peri-urban forests, and protected areas in Kanazawa, Japan, during public park closures ( 34 ). Furthermore, studies have shown that visiting urban green spaces during the COVID-19 pandemic did not increase the risk of infection, although context-specific measures should be considered to ensure the safety of visitors ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, context-specific measures should be considered to ensure the safety of visitors. Research has also shown that inequalities in access to green spaces have been exacerbated during the pandemic [59]. The pandemic's closure of parks and green spaces has narrowed the options for physical activity, which may impact vulnerable populations more than others.…”
Section: Discussionmentioning
confidence: 99%
“…They can encourage social interactions, foster social inclusion, stimulate innovation, and potentially alleviate depression and enhance self-awareness (Maurer et al, 2021;Wood et al, 2017;Tzoulas et al, 2007). The onset of COVID-19 in 2020 and subsequent social distancing regulations remarkably impacted outdoor activities, leading people to seek more recreation in open and green spaces instead of indoor leisure facilities such as cinemas and recreational centres (Yap et al, 2022;Ueno et al, 2022). The pandemic's lasting impact on people's recreation attitudes and behaviours remains uncertain (Kim et al, 2022;Senetra and Szczepańska, 2022).…”
Section: Introductionmentioning
confidence: 99%